Fabrication and Characterization of Chitosan/N-Phthaloyl Composite Membrane for DMFC Application - Christine Dyta Nugraeni; Lukman Atmaja; Nur Hayati; Mochammad Purwanto; Mardi Santoso; Yuli Kusumawati (Universitas Andalas, 2021)
Modified chitosan membrane is one of the promising membranes for polymer electrolyte membrane. Chitosan/N-phthaloyl chitosan composite membranes were fabricated to obtain high proton conductivity and low methanol permeability. Membranes were fabricated by casting method and solvent evaporation. Surface morphology, mechanical analysis, methanol permeability, and proton conductivity were used to characterize the overall properties. FT-IR spectra exhibited the presence of interaction of chitosan and n-phthaloyl/chitosan. SEM analysis showed that the surface roughness of composite membrane increases as the n-phthaloyl loading increases. The highest proton conductivity of synthesized membrane is at 2.4 mS.cm-1 and is higher than pristine chitosan membrane at 1.6 mS.cm-1. Moreover, with n-phthaloyl/chitosan addition, the methanol permeability was also improved. The correlation between proton conductivity and methanol permeability in composite membranes suggests that the blend has its potential in DMFC application.